2012
DOI: 10.1007/s12026-012-8288-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune predictors of cancer progression

Abstract: The immune system has multiple, complex, and sometimes opposing roles during cancer progression. While immune-compromised individuals have a higher incidence of cancers, inflammation is also associated with increased risk of disease progression. It is becoming apparent that simple measures of immune responses in the blood are of limited use in cancer. Instead, the importance of the exact identity and functional characteristics of tumor-infiltrating immune cells is increasingly recognized. This realization has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…not significant. natural killer cells and macrophages can affect tumor growth 39,[46][47][48] . We can use the proposed model to study the role of the immune system in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…not significant. natural killer cells and macrophages can affect tumor growth 39,[46][47][48] . We can use the proposed model to study the role of the immune system in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the intact immune system of the BALB/cJ mice, rejecting the tumor cells or to the cells being insufficient in number to re-model the local extracellular matrix. It has been known for many years that lymphocytes can affect tumor growth [19] and it has been found that natural killer cells, tumor-associated macrophages (TAMs), T-regulatory (Treg) and dendritic cells play a role in tumorigenesis [20][22]. Further, stimulation of all of these immune cell types has been shown in response to tumor implantation in BALB/cJ mice, those used in our model [23]–[25].…”
Section: Discussionmentioning
confidence: 99%
“…While the infiltration of effector lymphocytesisgenerally associated with a good prognosis, the infiltration of other immune cell populations (i.e.Myeloid Derived Suppressor Cells (MDSC) and T regulatory cells (Treg)) isthought to promote tumor progression by restraining tumor immunity and promoting neoplastic cell invasion and metastasis [1]. The identification of FOXP3, CD25 and CD4 as Treg associated markers prompted the investigation of the presence of this population in the immune infiltrate as a prognostic marker in various human malignancies [2].…”
Section: Introductionmentioning
confidence: 99%